2016
DOI: 10.1080/03019233.2016.1222046
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and application of oxygen lance in 120t BOF of PANSTEEL

Abstract: In this study, the numerical simulations were carried out to analyse the structure of the oxygen lance nozzle, the flow conditions of oxygen and the flow status of molten steel in the converter. Through the quantitative comparison of the mixing time of the bath under different angles of oxygen lance nozzle, the angle parameter of the oxygen lance nozzle is finalised to be 16°. There are significant improvements on the industrial applications of optimised oxygen lance 536-16, in which the average time of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The effect of the cyclone nozzle on the upward splashing behavior, penetrating depth, and reaction area of molten bath compared with a traditional oxygen lance were investigated for the purpose of proposing scientific theoretical basis for the lance design and the practical application of the cyclone oxygen lance. Some scholars have studied the influence of nozzle arrangement on the molten bath [4][5][6]. Some scholars have researched the influence of new designed nozzle on the molten bath [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the cyclone nozzle on the upward splashing behavior, penetrating depth, and reaction area of molten bath compared with a traditional oxygen lance were investigated for the purpose of proposing scientific theoretical basis for the lance design and the practical application of the cyclone oxygen lance. Some scholars have studied the influence of nozzle arrangement on the molten bath [4][5][6]. Some scholars have researched the influence of new designed nozzle on the molten bath [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that as the inlet pressure, ambient temperature, and Mach number increased, the jet axial velocity attenuation weakened [2][3][4], the length of the jet core area increased [5,6], and the dynamic pressure near the axis direction of the oxygen lance increased [7]; With respect to impact characteristics, the impact effect of the lance height and oxygen lance type on the molten bath was studied, and it was found that with an increasing lance height, the impact depth decreased and the impact area increased, and a better impact effect could be obtained by using nozzletwisted lances [8][9][10]; With respect to the flow field distribution, the effects of the oxygen lance nozzle structure, bottom blowing flow rate, and bottom blowing nozzle structure on the molten bath flow were studied. It was found that increasing the oxygen lance nozzle tilt angle improved the technical index, the average velocity of the steel increased with an increase in the bottom blowing flow rate, and the diameter changes of the bottom blowing nozzle had little influence on the flow law of liquid steel [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The research methods include theoretical design, water model simulation, numerical simulation, and industrial experimentation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Alam et al [17] used computational fluid dynamics (CFD) and a modified k-e turbulence model to simulate the influence of ambient temperature on a supersonic jet. They found that high temperature was beneficial for increasing the length of the core section of the jet, which was 2.5 times larger at 1800 K than that at room temperature.…”
Section: Introductionmentioning
confidence: 99%